Tutur Wiksu Pungu: Analisis Semiotik - Windya, Ida Made; Marselinawati, Putu Sri; Ariasa Giri, I Made (Widya Sandhi, 2025)
Understanding the teachings of Tutur Wikṣu Pungu in symbolic form is needed to conduct an in-depth study to reveal its meaning. This research aims to examine the symbolic meaning in the text so that it can contribute to Hindus as a whole. This qualitative research uses an interpretative descriptive approach based on Riffaterre's semiotic theory, focusing on symbolic elements. The research method used includes heuristic and hermeneutic reading techniques to explore the deep meaning of the symbols in the text. There are three main discussions in this research. First, the identification of the matrix (main idea) emphasises the importance of asceticism, self-control, and yoga-samadhi as a path to cosmic harmony between humans, nature, and God. Second, the model (symbolic elements), including the symbols of tri bhuvana (three worlds), pa ca mah? bh?ta (five elements of nature), Sang Hyang Aji as sacred knowledge, and guru as spiritual guide. The third variant (philosophical meaning) examines the philosophical meaning of the symbols. This research contributes to the study of Hindu theology by revealing how the teachings in Tutur Wikṣu Pungu can be relevant to religious life in the modern era.